Phenomenological Behavioural Problems Manifested by High School Students Enrolled in Subic National High School - Lonzon, Miriam De Ocampo; Espiritu, Raymond D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study determines the phenomenological behavioural problems manifested by high school students enrolled in Subic National High School and draws implications to address the behavioural issues. The study used qualitative research adhering to phenomenological methods, and data were thematically analyzed. Results of the study showed that most of the participants are between the ages of 28 and 32, most of the teacher's responders are female, the majority of the teacher's responses are teaching English, and the majority of participants are Teacher I. The common misbehaviour issues of the students inside the classroom are disruptive behaviours, truancy, and behavioural engagement. The factors that led to students' misbehaviour inside the school are biological, social factors, and internal factors. Participants encourage students to behave well inside the classroom by giving rewards and punishments, classroom activities, and creating a positive classroom environment. Suggested activities to make the students behave well inside the school are fostering a culture of reading, writing, listening, and speaking, interactive teaching and learning, and rewards and motivation. A program was proposed. The study recommends that teachers be trained to handle classroom management concerns and problems. Administrators, teachers, parents, and students must all collaborate to achieve a common aim of peace and harmony in well-managed schools. Students should be included as participants in future studies, and their impressions and comments about school punishment techniques should be recorded. Further study may be conducted to validate the findings of this research.